Comprehensive Assessment of Risk Factors for Colon Cancer in the Population of the North-West of Russia - V. N. Shumilova; A. E. Goncharov; E. L. Latariya; R. E. Topuzov; M. A. Bobrakov; V. V. Kolodzhieva; T. S. Fil; B. I. Aslanov (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. Colorectal cancer (CRC) is the third most common cancer in the world. In the Russian Federation, high rates of neglect in late diagnosis of colon cancer have been established. The study of the complex influence of social, clinical, anamnestic and dietary risk factors in the development of colorectal cancer is valuable in identifying risk groups for effective secondary prevention. Aims. Assessment of the importance of medical and social, clinical and anamnestic, alimentary-dependent factors as risk factors for colon cancer. Materials & Methods. To analyse the regional characteristics of CRC incidence, the database "Cancer diseases in the Northwestern Federal District" for 2010-2023 was used. To investigate the risk factors for CRC, a case- control study was organised in which patients over 18 years of age with or without diagnosed intestinal pathology (colorectal cancer, inflammatory bowel disease) were included. Results and discussion. Among patients with CRC, patients with advanced forms of the disease predominated: the proportion of CRC diagnosed at stage III and IV was 54% and 17% of newly diagnosed cases, respectively. When analyzing the data, no association was found between the risk of developing CRC and the presence of chronic diseases, oncological pathology, including CRC in relatives of the 1st and 2nd degree of kinship, alcohol abuse and smoking, as well as with most alimentary-dependent factors, with the exception of fried and smoked fish. Conclusions. Colon neoplasms are detected in the population of the Northwestern Federal District at late stages and when patients seek medical care independently. Significant attention in epidemiological studies should be paid to such a factor as eating fish after certain types of heat treatment (fried and smoked). prospects for further research, in our opinion, are related to the search for informative markers to identify risk groups, in particular factors associated with altered intestinal microbiota and colonisation of the intestine with potentially oncogenic microorganisms.